Mir-455-3p-1 represses FGF7 expression to inhibit pulmonary arterial hypertension through inhibiting the RAS/ERK signaling pathway. (May 2019) - Zhou, Chenghui; Chen, Yu; Kang, Wenying; Lv, Hong; Fang, Zhongrong; Yan, Fuxia; Li, Lihuan; Zhang, Weili; Shi, Jia
Abstract: Objective: To analyze the effects of miR-455-3p-1 and its possible mechanisms in pulmonary arterial hypertension (PAH). Methods: A microarray assay was used to examine the expressed genes between normal and PAH. The expressed genes in PAH was assessed by qRT-PCR. The targeted interaction between miRNAs and FGF7 was confirmed using a dual luciferase reporter assay. A CCK-8 assay and cell count were used to analyze the pulmonary artery smooth muscle cells (PASMCs) activity and proliferation level, respectively. Apoptotic PASMCs were detected by flow cytometry. In addition, the mRNA and protein expression levels of RAS/ERK signaling pathway were determined by qRT-PCR and a Western blot assay, respectively. A PAH rat model was used to identify the effects of miR-455-3p-1 in vivo . Results: FGF7 was upregulated in PAH. MiR-455-3p-1 was downregulated in PAH. MiR-455-3p-1 targeted FGF7. MiR-455-3p-1 decreased the expression of FGF7. Moreover, the effect of FGF7 on PASMCs was suppressed by miR-455-3p-1. MiR-455-3p-1 upregulation was associated with reduced mRNA and protein levels of core RAS/ERK signal genes, suggesting the inhibition of the RAS/ERK pathway. Furthermore, miR-455-3p-1 upregulation improved the RVSP, mPAP, ratio of RV/LV + S, CO and RV function of PAH rat model in vivo . Conclusion: Our findings illustrate a role for miR-455-3p-1 in modulating FGF7-RAS/ERK signaling and suggest that an agomir of miR-455-3p-1 could inhibit the proliferation of PASMCs and mitigate PAH in vivo .